PENGARUH UKURAN PERUSAHAAN, INVESTMENT OPPORTUNITY SET, DAN PROFITABILITAS TERHADAP KEBIJAKAN DIVIDEN DENGAN DEBT TO EQUITY RATIO DAN KEPEMILIKAN INSTITUSIONAL SEBAGAI MODERATING VARIABLE - Iin Fahriyani (Riset Akuntansi Keuangan, 2016)
This study tested the effect of firm size, investment opportunity set (IOS), and the profitability of dividend policy with debt to equity ratio (DER) and institutional ownership as moderating variables. Tests conducted on 23 manufacturing companies listed on the Indonesian Stock Exchange in the year 2006-2010.The analysis showed that the size of the company, IOS, and profitability has no effect on dividend policy, nor with the DER and institutional ownership are not moderating variables. Additional tests of difference test statistical to determine differences of dividend policy on growth firms and non-growth firms indicated that there is no difference between the dividend payout policy on growth firms and non-growth firms, which means dividend policy does not depend on the IOS.Implications of this research are providing consideration in determining the appropriate dividend policy for the management and investment decisions for investors who expect any dividends received by viewing information based on the numbers in the financial statements and other information that is expected to increase dividend payments.